PERBEDAAN KADAR ALBUMIN DALAM DARAH SEBELUM DAN SESUDAH PEMBERIAN AIR KELAPA HIJAU PADA PEKERJA PAINTING (ALBUMIN DIFFERENCES IN BLOOD BEFORE AND AFTER GIVING GREEN COCONUT WATER ON WORKERS PAINTING DEPARTEMENT) - Budi Waloyo; Onny Setiani; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Background: Departement of painting on karoseri X industry potentially provided lead exposure to workers, because of lead that contained in paint raw materials used. The lead exposure lead into the liver and may causing disruption on the production of albumin. In the green coconut water contain tannins substance that serves as a binder for lead in the blood and body fluids. Methods: This research using a quasi-experimental design with one group pretest-posttest design. The treatment done with the provision of green coconut water for 5 days. Samples that used in this research were 32 workers painting in karoseri X. The measurement method using the albumin level hematology analyzer, at a wavelength of 546 nm. The level of albumin in the blood that is carried out in the laboratory using Spectrometer- Atomic Absorption (AAS) method. Results: There was a differences between the levels of albumin with t-test significance value (p-value) = 0.013 (p <0.05). Conclusion: Differences between the levels of albumin in the blood workers painting departement before giving green coconut water and after giving green coconut water.